Salt – ressurs og handelsvare i middelalderen - Kjetil Loftsgarden (Heimen)
<?xml version="1.0" encoding="UTF-8"?><!DOCTYPE p PUBLIC "-//W3C//DTD HTML 4.01 Transitional//EN" "http://www.w3.org/TR/html4/loose.dtd"> Throughout the Middle Ages there was a surplus production ofsalt in several of the inner fjords of Norway. For farms in theseareas, salt production was part of a diversified economy where a numberof resources could be utilised, such as animal husbandry, agricultureor fishing. Salt was produced by heating seawater in large shallowiron pans. This required substantial amounts of firewood, thus makingthe inner fjord areas especially suited for salt production. Another likely contributing factor for the surplus productionof salt in the inner fjord areas was proximity to mountainous andvalley regions, where salt had to be imported. Place names and writtensources indicate that salt was an important commodity between innerfjords and the inlands of South Norway.